Specific CD8+ TCR Repertoire Recognizing Conserved Antigens of SARS-CoV-2 in Unexposed Population: A Prerequisite for Broad-Spectrum CD8+ T Cell Immunity - Wei Hu; Meifang He; Xiaoning Wang; Qiang Sun; Ming Kuang (Vaccines, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has developed variants escaping neutralization antibody immunity established against the original virus. An understanding of broad-spectrum adaptive immunity, including CD8+ T cell immunity to wide range of epitopes, could help translational efforts to improve coronavirus disease 2019 (COVID-19) prevention and therapy. However, there have been few direct studies in which such immunity exists in a population. Methods: We selected SARS-CoV-2-conserved structural peptides that are not prone to mutation as antigens for broad-spectrum CD8+ T cell immunity. Peripheral blood mononuclear cells (PBMCs) from unexposed healthy donors were stimulated with these peptides in vitro and CD8+ T cell-specific response was monitored. The conserved peptide-specific CD8+ T cells were sorted for T cell receptor (TCR) repertoire sequencing. The presence of specific complementary determining region 3 (CDR3) clones was analyzed in a healthy cohort. Results: For each structural protein, including S, E, M, N, the conserved peptides could potentially provide the largest number of major histocompatibility complex-I (MHC-I) epitopes in the Oriental and Caucasian populations. For conserved peptides from spike (S), envelope (E), membrane (M), nucleocapsid (N) proteins, we found that there were no cross-reactive memory T cells in the unexposed individuals. Instead, their T cells contain naïve TCR repertoire recognizing these conserved peptides. Using TCR sequencing and CDR3 clustering for the conserved peptides specific T cells, we found that the recovered patients had a higher proportion of TCR repertoire similar with that of specific CD8+ T cells in unexposed individuals. Meanwhile, CDR3 clones of the above T cells were widely present in the healthy population. Conclusions: This study provides evidence of broad-spectrum SARS-CoV-2 specific CD8+ TCR repertoire in unexposed healthy population, which is implicated in the development and implementation of broad-spectrum vaccines against COVID-19.